The Multilingual Corpus of Survey Questionnaires: A tool for refining survey translation - Zavala-Rojas, Diana; Sorato, Danielly; Hareide, Lidun; Hofland, Knut (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2022)
This article describes the design and compilation of the Multilingual Corpus of Survey Questionnaires (MCSQ), the first publicly available corpus of international survey questionnaires. Version 3.0 (Rosalind Franklin) is compiled from questionnaires from the European Social Survey, the European Values Study, the Survey of Health, Ageing and Retirement in Europe, and the Wage Indicator Survey in the (British) English source language and their translations into eight languages (Catalan, Czech, French, German, Norwegian, Portuguese, Spanish and Russian). Documents in the corpus were translated with the objective of maximising data comparability across cultures. After contextualising aims and procedures in survey translation, this article presents examples of two types of problematic translation outcomes in survey questionnaires: The first type relates to the choice of idiomatic terms or fixed expressions in the source text. The second type relates to cases where the semantic variation of translation choices exceeds the scope allowed to maintain the psychometric properties across languages. With these examples, we aim to demonstrate how corpus linguistics can be used to analyse past translation outcomes and to improve the methodology for translating questionnaires.